KEAKTIFAN BERLITURGI ORANG MUDA KATOLIK DI STASI SEBABI PAROKI ST. JOAN DON BOSCO SAMPIT - Paulus Junaidi; Silvester Adinuhgra; Paulina Maria E. W (Sepakat : Jurnal Pastoral Kateketik, 2021)
This study aims to determine the liturgical activities of OMK in Sebabi Community of St. Joan Don Bosco Parish of Sampit. The intended liturgical activity is the participation of OMK in taking part in liturgical tasks, such as participating in the celebration of the Eucharist, worship of the word without a priest, singing practice (choir), as lector I or II in the Eucharistic celebration , as psalmist and so on. This study used qualitative research methods. The source of data in this study was OMK in the Sebabi Community of St. Joan Don Bosco Parish of Sampit. Data collection techniques used in this research are interview, observation, and documentation techniques. The place of research is in the Sebabi community of St. Joan Don Bosco Parish of Sampit. The informants in this study were ten of them who were grouped into three, namely a Priest as a mentor of OMKs, community leader and OMK. The research steps include determining the theme, informant profiles, interview with informants, reflection, implications, synthesis and prospects.